Ultrasound-assisted enzymatic extraction of dark tea total polyphenols - Shao, Jinhua; Xiao, Xinsheng; Li, Yuhang; Chen, Bo; Xing, Lei; Zhu, Zhiyong; Qi, Chengmei (Frontiers in Nutrition, 2025)
Tea polyphenols have become the most biologically active components in tea, and they are also one of the key factors determining the color, flavor, health benefits. This study used dark tea as the raw material and employed the Plackett Burman method to screen for 8 factors that may affect the extraction of dark tea total polyphenols. Box Behnken response surface methodology was used to further optimize the four most important variables. At a solid-liquid ratio of 1:50, enzyme dosage of 2.5%, pH of 5.6, enzymatic hydrolysis temperature of 45°C, enzymatic hydrolysis time of 50 min, ethanol volume fraction of 50%, ultrasonic temperature of 72°C, and ultrasonic time of 50 min, the highest extraction amount of dark tea total polyphenols was obtained. Compared with the ethanol reflux extraction method, the extraction amount of dark tea total polyphenols increased by about 43.38%, and compared with the ultrasonic assisted extraction method, the extraction amount of dark tea total polyphenols increased by about 30.45%. Ultrasonic assisted enzymatic extraction of dark tea total polyphenols has the strongest antioxidant activity. The optimized process of ultrasound assisted enzymatic extraction can increase the extraction amount and antioxidant activity of dark tea total polyphenols, reduce extraction time, and lower extraction temperature. Ultrasonic assisted enzymatic method is simple, efficient, and can be industrially promoted, and it also has reference value for the extraction of other plant active ingredients.